Critical Review of Police Performance in Upholding Law Enforcement and Human Rights in Indonesia - Ningsih, Riska Kurnia; Hadi Tuasikal (Universitas Semarang, 2025)
This study critically examines the effectiveness of the Indonesian National Police (Polri) in enforcing the law and protecting human rights (HAM), specifically within the framework of national legal instruments. Despite the established legal foundation, including Law No. 2 of 2002 on the Police and Regulation of the Chief of Police No. 8 of 2009, the persistent violations of human rights by police officers highlight significant implementation gaps. These violations have led to a notable decline in public trust, raising questions about the adequacy of current legal frameworks in ensuring the protection of human rights. The urgency of this research lies in identifying the systemic failures in Polri’s performance, particularly the lack of consistent application of human rights principles in policing practices. By analyzing legal documents, case law, and reports from institutions such as Komnas HAM, this study reveals that the ineffective implementation of existing regulations, coupled with weak internal oversight and a culture of impunity, significantly hampers Polri’s ability to uphold human rights. The findings contribute new insights into the disconnect between normative legal standards and their practical application, offering a nuanced understanding of the challenges in reforming law enforcement practices. To address these challenges, the study recommends strengthening legal training, enhancing monitoring mechanisms, and fostering a shift in organizational culture within Polri to ensure better compliance with human rights standards and restore public trust.